Manduda Dance in Simalungun Community Dancing Style in a Contextual Perspective - Ruth Hertami Dyah Nugrahaningsih (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to explain: 1) the relationship of body attitude in Manduda Dance with the activities of the Simalungun community; 2) the relationship between the type of transition in Manduda dance and the activities of Simalungun community; 3) the relationship between the number of active body part in Manduda dance and the patterns of daily activities of Simalungun community; 4) the relationship between business forms and the patterns of study is the formulation of dance style in Manduda dance on Simalungun community in a contextual perspective. The research method used is a qualitative-anthropological approach, specifically called choreometrics, which is to analyze the relationship between dance movements including body attitude, type of transition, the number of active body part, and the forms of business with patterns of daily community activities. Observation, documentation, and interview techniques were used to collect data and then the triangulation data analysis process was carried out to obtain the credibility of the data. The results of this study found that both viewed from body attitude, type of transition, the number of active body part, as well as the forms of effort contained in Manduda dance, were very closely related to the patterns of daily activities of Simalungun community patterned with paddy harvesting agricultural activities.